Etiology of obsessions and compulsions: General and specific genetic and environmental factors. (30th March 2016) - Taylor, Steven; Asmundson, Gordon J.G.; Jang, Kerry L.
Abstract: Evidence suggests that a general etiologic factor plays a role in many forms of psychopathology, possibly including obsessive–compulsive (OC) symptoms. A twin study ( N= 307 twin pairs) of OC symptoms and their endophenotypes was conducted to investigate the role of general and symptom-specific etiologic factors. OC symptoms and endophenotypes were found to have complex etiologies, being shaped by OC-specific genetic and environmental factors, and by genetic and environmental factors that shape psychopathology in general. Understanding the general and specific etiologies underlying OC symptoms has implications for improving treatments outcomes through the development of therapies that target general and/or specific factors. Highlights: OC symptoms share, in part, common etiologies with other forms of psychopathology. OC symptoms are also shaped by symptom-specific etiological factors. OC symptoms have a complex etiologic architecture.